Lactational and geographical variation in the concentration of six oligosaccharides in Chinese breast milk: a multicenter study over 13 months postpartum - Liu, Shuang; Mao, Yingyi; Wang, Jin; Tian, Fang; Hill, David R.; Xiong, Xiaoying; Li, Xiang; Zhao, Yanrong; Wang, Shuo (Frontiers in Nutrition, 2023)
Understanding the variations of oligosaccharide in breast milk contribute to better study how human milk oligosaccharides (HMOs) play a role in health-promoting benefits in infants. Six abundant HMOs, 2'-fucosyllactose (2'-FL), 3-fucosyllactose (3-FL), Lacto-N-tetraose (LNT), Lacto-N-neotetraose (LNnT), 3'-sialyllactose (3'-SL) and 6'-sialyllactose (6'-SL), in breast milk collected at 0-5 days, 10-15 days, 40-45 days, 200-240 days, and 300-400 days postpartum from six locations across China were analyzed using high-performance anion-exchange chromatography-pulsed amperometric detector. The results showed that, the concentration of individual HMO fluctuated dynamically during lactational stages. The median ranges of 2'-FL, 3-FL, LNT, LNnT, 3'-SL, and 6'-SL across the five lactational stages were 935-2865 mg/L, 206-1325 mg/L, 300-1473 mg/L, 32-317 mg/L, 106-228 mg/L, and 20-616 mg/L, respectively. The prominent variation was observed in the content of 6'-SL, which demonstrates a pattern of initial increase followed by a subsequent decrease. Among the five lactational stages, the transitional milk has the highest concentration, which was 31 times greater than the concentration in mature milk at 300-400 days postpartum, where the content is the lowest. Geographical location also influenced the content of HMOs. LNT and LNnT were the highest in mature milk of mothers from Lanzhou among the six sites at 40-240 days postpartum. Breast milks were categorized into two groups base on the abundance of 2'-FL (high and low). There was no significant difference in the proportions of high and low 2'-FL phenotypes among the six sites, and the percentages of high and low 2'-FL phenotypes were 79% and 21%, respectively, across all sites in China. This study provided a comprehensive dataset on 6 HMOs concentrations in Chinese breast milk during the extended postpartum period across a wide geographic range and stratified by high and low 2'-FL phenotypes.